TRADE IS AN IMPORTANT FACTOR INCREASING THE COMPETITIVENESS OF THE COUNTRY'S ECONOMY (Marketing Journal, 2025)
This article explores topics such as the role and significance of trade in the national economy, the unique features of trade, the establishment of a robust infrastructure in the trade sector, the enhancement of effective competitiveness, and the country's active participation in international trade relations.
Keywords: trade; retail trade; goods; consumption; distribution; trade management; trade networks; marketing; advertising; trade infrastructure; trading enterprises; competitiveness; market entities; trade entities